Evaluation of Chinese-Herbal-Medicine-Induced Herb-Drug Interactions: Focusing on Organic Anion Transporter 1. (4th September 2012) - Lin, Chang-Ching; Fan, Hsien-Yuan; Kuo, Chien-Wen; Pao, Li-Heng
Abstract : The consumption of Chinese herbal medicines (CHMs) is increasing exponentially. Many patients utilize CHMs concomitantly with prescription drugs in great frequency. Herb-drug interaction has hence become an important focus of study. Transporter-mediated herb-drug interactions have the potential to seriously influence drug efficacy and toxicity. Since organic anion transporter 1 (OAT1) is crucial in renal active secretion and drug-drug interactions, the possibility of modulation of OAT1-mediated drug transport should be seriously concerned. Sixty-three clinically used CHMs were evaluated in the study. An hOAT1-overexpressing cell line was used for the in vitro CHMs screening, and the effective candidates were administered to Wistar rats to access renal hemodynamics. The regulation of OAT1 mRNA expression was also examined for further evidence of CHMs affecting OAT1-mediated transport. Among all the 63 CHMs, formulae Gui Zhi Fu Ling Wan (GZ) and Chia Wei Hsiao Yao San (CW) exhibited significant inhibitions on hOAT1-mediated [ 3 H]-PAH uptake in vitro and PAH clearance and net secretion in vivo . Moreover, GZ showed concentration-dependent manners both in vitro and in vivo, and the decrease of rOAT1 mRNA expression indicated that GZ not only inhibited function of OAT1 but also suppressed expression of OAT1.